Comparative Analysis of Complications While Using Various Biopsy Techniques of Prostate Gland - Atoyev Sherzod Sharifovich (European Science Publishing, 2023)
Nowadays the increase in the incidence of prostate cancer on last decade is more than half of situations of PCa. The average annual growth rate is 7.76%. Great importance in diagnosis and subsequent choice of treatment tactics for the patient has histological verification of prostate cancer. Currently, the most common method is transrectal “blind” ultrasound-guided prostate biopsy, which does not have sufficient sensitivity and specificity for detecting prostate cancer, and the morphological result contains limited information about the aggressiveness and stage of the disease. Multiparametric magnetic resonance imaging is currently the most sensitive and a specific imaging method for diagnosing prostate cancer, techniques are increasingly used in clinical practice targeted prostate biopsy.
Keywords: prostate cancer, prostate biopsy, magnetic resonance imaging, saturation prostate biopsy, transperineal combined biopsy.